Broadband Ultrafast Dynamics of Refractory Metals: TiN and ZrN. Issue 19 (12th July 2020) - Diroll, Benjamin T.; Saha, Soham; Shalaev, Vladimir M.; Boltasseva, Alexandra; Schaller, Richard D.
Abstract: Transition metal nitrides have recently gained attention in the fields of plasmonics, plasmon‐enhanced photocatalysis, photothermal applications, and nonlinear optics because of their suitable optical properties, refractory nature, and large laser damage thresholds. This work reports comparative studies of the transient response of films of titanium nitride (TiN), zirconium nitride (ZrN), and gold (Au) under femtosecond excitation. Broadband transient optical characterization helps to adjudicate earlier, somewhat inconsistent reports regarding hot electron lifetimes based upon single wavelength measurements. These pump–probe experiments show sub‐picosecond transient dynamics only within the epsilon‐near‐zero window of the refractory metals. The dynamics are dominated by photoinduced interband transitions resulting from ultrafast electron energy redistribution. The enhanced reflection modulation in the epsilon‐near‐zero window makes it possible to observe the ultrafast optical response of these films at low pump fluences. These results indicate that electron–phonon coupling in TiN and ZrN is 25–100 times greater than in Au. Strong electron–phonon coupling drives the sub‐picosecond optical response and facilitates greater lattice heating compared to Au, making TiN and ZrN promising for photothermal applications. The spectral response and dynamics of TiN and ZrN are only weakly sensitive to pump fluence and pump excitation energy. However, the magnitude of the response is much greater at higher pump photon energies and higher fluences, reaching peak observed values of 15% in TiN and 50% in ZrN in the epsilon‐near‐zero window. Abstract : Broadband ultrafast pump–probe measurements of titanium nitride and zirconium nitride films reveal sub‐picosecond optical dynamics in the epsilon‐near‐zero window and large lattice heating. This finding is attributed to transiently modulated electron energy distributions, which effect interband oscillator strength and strong electron–phonon coupling which rapidly cools the electron plasma and heats the lattice.